A long-term follow-up study of adults with Chiari malformation type I combined with syringomyelia - Hu, Yan; Zhang, Mingchu; Duan, Chengcheng; Song, Dengpan; Wei, Mingkun; Guo, Fuyou (Frontiers in Neurology, 2023)
There is a considerable amount of controversy regarding the treatment and prognosis of adult patients with Chiari malformation type I(CM-Ⅰ)at home and abroad; furthermore, there is no large-sample, long-term, follow-up studies have examined CM-Ⅰ patients with syringomyelia (SM) comparing posterior fossa decompression with resection of tonsils (PFDRT) versus posterior fossa decompression with duraplasty (PFDD) .Objective: This study retrospectively analyzed the factors affecting the treatment and long-term prognosis of adults with CM-Ⅰ combined with SM.We retrospectively analyzed data from 158 adult CM-I patients combined with SM who underwent PFDRT or PFDD , including 68 patients in group PFDRT and 90 patients in group PFDD. We examined the clinical manifestations, imaging features of patients. Clinical outcomes were assessed using the CCOS, and radiographic outcomes were indicated by the syrinx remission rate. Multivariate logistic regression analysis and multiple linear regression analysis were used to explore the relevant factors affecting the long-term prognosis of patients.Results: This study showed that compared with preoperative patients in group PFDRT and group PFDD, the sensory impairment, cough-related headache, and movement disorder were significantly improved (P<0.01); meanwhile, the diameter of the syrinx and the volume of the syrinx decreased significantly (P<0.001).Additionally, the study found that there were significant difference in the syrinx remission rate (P=0.032) and the clinical cure rates (P =0.003) between the two groups. Multivariate logistic regression analysis showed that age (P =0.021), cerebellar-related symptoms (P=0.044), preoperative cisterna magna volume (P =0.043) and peak systolic velocity (P=0.036) were independent factors for clinical outcomes. Multiple linear regression analysis showed that different surgical procedures were positively correlated with the syrinx remission rate (P=0.014), while preoperative syrinx diameter (P =0.018) and age (P=0.002) were negatively correlated with the syrinx remission rate.In conclusion, this study suggested that, in a long-term follow-up, although both surgical procedures are effective in treating patients with CM-I and SM, PFDRT is better than PFDD; age and cerebellar-related signs independently affect patient's prognosis. Additionally, an effective prognosis evaluation index can be developed for patients, which based on imaging characteristics, such as preoperative cisterna magna volume, and preoperative cerebrospinal fluid (CSF) hydrodynamic parameters to guide clinical work.